Wild Things 3 - Susan Ward; Arcieri, Leila; Washington, Isaiah; Chieffo, Michael; Ashby, Linden (USA, 2004)
Based on the hot movie Wild Things, Wild Things 2 sees teenage bad girls Maya and Britnney go on a sex and killing spree to win millions
Keywords: Thriller